ANALISIS LITERASI KEUANGAN, PERSEPSI KEMUDAHAN FINTECH P2P LENDING DAN PEMAHAMAN REGULASI OJK TERHADAP KEPUTUSAN PENGGUNAAN SHOPEE PINJAM - Astrian Hessy Defitri (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
This study aims to determine Financial Literacy, Perceptions of the Ease of Fintech P2P Lending and Understanding of Ojk Regulations on the Decision to Use Shopee Pinjam which was conducted to Shopee Pinjam users as research subjects. The sample in this study were 75 respondents with the sampling technique used was using the probability sampling method (random sampling) using the distribution of questionnaires. The data analysis technique used is the SEM-PLS analysis technique with a calculation process supported by SmartPLS 4.0 software. The results of this study indicate that the variables of Financial Literacy, Perception of the Ease of Fintech P2P Lending, and Understanding Ojk Regulations have a positive and significant effect on the Decision to Use Shopee Pinjam with an R-square (R2) value of 0.768 or 76%.